A re‐evaluation of the role of rotational forceps: retrospective comparison of maternal and perinatal outcomes following different methods of birth for malposition in the second stage of labour. Issue 10 (21st March 2013) - Tempest, N; Hart, A; Walkinshaw, S; Hapangama, DK
Abstract : Objective: To compare the outcomes of operative cephalic births by Kielland forceps (KF), rotational ventouse (RV), or primary emergency caesarean section (pEMCS) for malposition in the second stage of labour in modern practise. Design: Retrospective observational study. Population: Data were included from 1291 consecutive full‐term, singleton cephalic births between 2 November 2006 and 30 November 2010 with malposition of the fetal head during the second stage of labour leading to an attempt to deliver by KF, RV or pEMCS. Methods: Maternal and neonatal outcomes of all KF births were compared with other methods of operative birth for malposition in the second stage of labour (RV or pEMCS). Main outcome measures: Achieving a vaginal birth was the primary outcome and fetal (admission to special care baby unit, low cord pH, low Apgar, shoulder dystocia, Erb's palsy) and maternal (massive obstetric haemorrhage—blood loss of >1500 ml, sphincter injury, length of stay in hospital) safety outcomes were also recorded. Results: Women were more likely to need caesarean section if RV (22.4%) was selected to assist the birth rather than KF (3.7%; adjusted odds ratio 8.20; 95% confidence interval 4.54–14.79). Births by KF had a rate of adverse maternal and neonatal outcomes comparable to those by RV and pEMCS in the second stage for malposition. Conclusions: Our results suggest that, in experienced hands, assisted vaginal birth by KF is likely to be the most effective and safe method to prevent the ever rising rate of caesarean sections when malposition complicates the second stage of labour.